Statistical Characteristics of Polymer Grouting Material Microstructure - Juan Wang; Xun Li; Hongyuan Fang; Juan Zhang; Jinping Li (Advances in Civil Engineering)
The two-component foaming polyurethane is a kind of grouting material that has recently been widely used in engineering structural repair. Its physical and mechanical properties are closely related to its microstructure. Therefore, the qualitative and quantitative analysis of polymer microstructure has always been a research hotspot. The statistical characteristics of polymer grouting material microstructure are investigated by six groups of specimens with different densities, and the density varies from 0.1 to 0.6 g/cm3. The microstructure morphology of polymer was observed and described by scanning electron microscopy (SEM), and the microstructure feature parameters were extracted and calculated by image processing technology. The quantitative analysis of section cell roundness distribution, cell diameter distribution, and polymer porosity shows that low-density polymer materials have anisotropy. While the density exceeds 0.3 g/cm3, the cell structure tends to be spherical. The section cell diameters obey a normal distribution, and when the density increases, the cell diameter decreases. The porosity of the polymer has a linear negative correlation with the density. The polymer matrix has a density of 1.21 g/cm3. The microstructural information obtained in this study will help establish a cell-based model to explain the mechanical response of rigid polymer foams.